Միջնադարեան հայ կոմպոզիտորներ - Արամ Երեմեան (Տպարան Սրբոյ Յակոբեանց)
Գրիգոր Պահլաւունի.-Ներսէս Շնորհալի.-
Keywords: Medieval History; Auxiliary Sciences of History; History; Biography; Music and Books on Music; Music